Tau alternative splicing in familial and sporadic tauopathies. (20th July 2012) - Niblock, Michael; Gallo, Jean-Marc
Abstract : Six tau isoforms differing in their affinity for microtubules are produced by alternative splicing from the MAPT (microtubule-associated protein tau) gene in adult human brain. Several MAPT mutations causing the familial tauopathy, FTDP-17 (frontotemporal dementia with parkinsonism linked to chromosome 17), affect alternative splicing of exon 10, encoding a microtubule-binding motif. Advanced RNA analysis methods have suggested that levels of exon 10-containing MAPT mRNA are elevated in Alzheimer's disease. Furthermore, the MAPT H1 haplotype, associated with Alzheimer's disease, promotes exon 10 inclusion in MAPT mRNA. Thus an accurate regulation of tau alternative splicing is critical for the maintenance of neuronal viability, and its alteration might be a contributing factor to Alzheimer's disease. Tau alternative splicing could represent a target for therapeutic intervention to delay the progression of pathology in familial as well as sporadic tauopathies.